RESEARCH ON THE EVOLUTION OF THE LEADERSHIP MODEL IN THE MODERN DISTRIBUTION SYSTEM - STETSENKO, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the evolution of leadership models in a VUCA environment characterized by instability, uncertainty, complexity, and ambiguity. The impact of these factors on distribution companies is analyzed, including changes in consumer behavior, personnel, and business processes. The results of the study show that the shortening of product life cycles and the growth of customer expectations have significantly complicated management processes. For example, technological innovations have reduced the product update cycle to 6 months. We analyze examples of companies such as Amazon and Walmart, which use demand forecasting systems to reduce logistics costs by 15–20%. The article develops practical recommendations for improving management approaches and proposes a leadership model adapted to modern challenges, in particular through the introduction of personalization and innovation. This study provides relevant information for improving the efficiency of distribution management in the face of global changes.
Keywords: VUCA environment; leadership; distribution; innovation; personalization; adaptation